MONITORING THE EFFECTIVENESS OF ANTITHROMBOLYTIC PREPARATIONS IN THE TREATMENT OF CORONARY HEART DISEASE - Khodjaeva D. I; Fayzieva K. M. (International Engineering Journal For Research & Development, 2021)
The criteria for an "ideal" anticoagulant are formulated and the compliance of currently known direct anticoagulants with these criteria is shown. Current recommendations for laboratory monitoring of the effects of "old" direct anticoagulants (unfractionated and low-molecular-weight heparins) and new-generation direct anticoagulants (thrombin and factor Xa inhibitors)are presented in patients of different risk groups